Sculptures on the enclosure walls of the Mandakini Kund - Temples of India Project Team (Jio Institute, 2024)
Inside the enclosure walls, numerous sculptures are displayed, including depictions of goddesses, deities such as Brahma, Vishnu, and Mahesha, dikapalas (deities for cardinal directions), surasundaris (celestial damsels) and vyalas (mythical composite creatures). They are arranged sporadically, lacking a clear order or sequence, indicating that they were not initially intended to decorate the reservoir.